2009
DOI: 10.1111/j.1740-0929.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbage intake on goat performance in the mediterranean type natural pastures

Abstract: This study aimed at identifying changes in natural pastures during the grazing season and investigating the effects of these changes on pasture feeding potential for high yielding dairy goats. During the study, 12 dairy goats were grazed on a 1.5 ha natural pasture for three months from April to June in 2003, 2004 and 2005. The goats were fed 0.5 kg/day of concentrate as a supplement during the grazing season. Botanical composition, herbage production and intake, crude protein (CP), neutral detergent fiber (ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In concordance with this, Hakyemez et al (2009) investigated the potential use of natural pastures for high yielding dairy goats and found that CP content of the pasture decreased but the structural carbohydrates increased as the grazing season proceeded. However, Sanon et al (2008) concluded that forage eaten by goats with a CP content of above 10 g/ 100g DM, have potential for improving N to ruminants.…”
Section: Resultsmentioning
confidence: 89%
“…In concordance with this, Hakyemez et al (2009) investigated the potential use of natural pastures for high yielding dairy goats and found that CP content of the pasture decreased but the structural carbohydrates increased as the grazing season proceeded. However, Sanon et al (2008) concluded that forage eaten by goats with a CP content of above 10 g/ 100g DM, have potential for improving N to ruminants.…”
Section: Resultsmentioning
confidence: 89%
“…Jung and Allen (1995) reported that the cell wall content affected the intake and digestibility of forage by ruminants. Furthermore, Hakyemez et al (2009) reported that the season of the year strongly affected the plant nutritive value. In addition, El-Shaer (2010) noted that most desert plants in Egypt are nutritious during the wet season and can meet the maintenance requirements of grazing small ruminants, and that was not the case during dry seasons.…”
Section: Body Weight Changes Feed Intake and Digestibilitymentioning
confidence: 98%